Interpersonal Neural Entrainment during Early Social Interaction. Issue 4 (April 2020) - Wass, Sam V.; Whitehorn, M.; Marriott Haresign, I.; Phillips, E.; Leong, V.
Abstract : Currently, we understand much about how children's brains attend to and learn from information presented while they are alone, viewing a screen – but less about how interpersonal social influences are substantiated in the brain. Here, we consider research that examines how social behaviors affect not one, but both partners in a dyad. We review studies that measured interpersonal neural entrainment during early social interaction, considering two ways of measuring entrainment: concurrent entrainment (e.g., 'when A is high, B is high' – also known as synchrony) and sequential entrainment ('changes in A forward-predict changes in B'). We discuss possible causes of interpersonal neural entrainment, and consider whether it is merely an epiphenomenon, or whether it plays an independent, mechanistic role in early attention and learning. Highlights: Social factors exert transient influences on the brains of both partners during an interaction. Interpersonal neural entrainment during early learning interactions has been documented at multiple temporal scales, replicating findings with adults and animals. Neural entrainment can be a consequence of behavioral coordination, but it can also arise in the absence of behavioral coordination: shared understanding involves temporally co-occurring patterns of brain activity. Neural entrainment may influence learning in multiple ways; for example, by allowing the sender to ensure information delivered arrives at an optimal time for encoding by the receiver.